Molekularni mehanizmi tvorbe zasevkov - Hudler, Petra (Medicinski razgledi, 2010)
The spread of metastases from a primary site through blood or the lymphatic system, which results in the establishment of secondary tumors in distant locations, is the main cause of death in cancer patients. Recent molecular andclinical studies have expanded knowledge of mechanisms implicated in metastasis formation. The development of cells with metastatic potential requires a coordinated expression and function of genes in both tumor cells and cells from surrounding tissues. All of the events involved in the metastatic cascade (Le. angiogenesis, adhesion, migration, invasion, and growth) also play an important role in normal biological processes, such as reproduction, embryogenesis, wound healing, smooth muscle cell migration, lymphocyte trafficking and liver regeneration. The identification of moleculesand signal pathways that contribute to metastasis is important for developing novel diagnostic and/or prognostic tests and for discovering novel therapeutic strategies to combat metastatic disease.
Keywords: diagnostika; novotvorbe; tumor; rak (medicina); metastaze; tumorske celice; molekularni mehanizmi